Fischer-tropsch synthesis: Differences observed in local atomic structure and selectivity with pd compared to typical promoters (Pt, Re, Ru) of Co/Al 2O 3 catalysts - Jacobs, G.; Ma, W.; Gao, P.; Todic, B.; Bhatelia, Tejas; Bukur, D.; Khalid, S.; Davis, B. (2012)
Pd was examined as a promoter for Fischer- Tropsch synthesis, and its effects on cobalt oxide reduction and product selectivities relative to commonly used promoters (i.e., Pt, Re, and Ru) at atomically equivalent levels were compared. Pd was identified to promote cobalt oxide reduction to even lower temperatures than Pt and Ru. However, Pd addition deleteriously affected product selectivity, and a clear shift to favor light products was observed. XANES analysis of an activated model catalyst revealed that Pd was in the reduced state. Local atomic structure was examined by EXAFS. Unlike Pt, Re, and Ru promoters, where previous investigations by groups such as Dr. Guczi's and ours have only observed coordination of the promoter with cobalt, Pd displayed both direct coordination to Co as well as other Pd atoms. The results suggest that this feature may be responsible for the measurably higher light gas selectivities observed. Â© Springer Science+Business Media, LLC 2012.